Pembelajaran Kaligrafi Dasar Untuk Melatih Kemahiran Menulis Bahasa Arab Bagi Siswa Maderasah Ibtidaiyah - Dedi Mustofa (DIMAR: Jurnal Pendidikan Islam, 2020)
The Calligraphy (Khat) is one of the local content lessons that has been taught at MI Al Mubarok Uman Agung from grade 1 to grade 6. Besides teaching the rules of beautiful writing it also trains children from an early age to be able to write Arabic letters properly and correctly so that they do not give rise to readings, meanings and interpretations that are wrong. This research is a qualitative study that took place at MI Al Mubarok Uman Agung. Data collection is done by conducting observations, interviews and documentation. Data analysis is done by giving meaning to the data collected and then conclusions drawn. The results of this study indicate that the calligraphy learning process is going well and many students pay attention and are interested in calligraphy learning. In addition, basic calligraphy is very supportive to train students' writing skills from the elementary level, as has been taught at MI Al Mubarok Uman Agung, Students can find it easy to understand Arabic lessons when teachers write Arabic texts properly and correctly, and vice versa Arabic texts will be difficult to understand if the writing is not in accordance with the rules of good writing and correct.